Pengaruh Electronic Word Of Mouth, Online Review, Dan Sensitivitas Harga, Terhadap Niat Beli Kosmetik Emina Di Kalangan Generasi Z Di Kabupaten Aceh Barat - Arba’iah, Arba’iah; Siddiq, Rahmad (INDO PUBLISHING, 2026)
This study aims to examine the influence of electronic word of mouth, online reviews, and price sensitivity on the purchase intention of Emina cosmetics among Generation Z in West Aceh. The background of this research is driven by the phenomenon of increasing digital activity among the youth, which influences purchasing behavior patterns, particularly regarding domestic cosmetic products. The research methodology employed is quantitative with an associative approach. Data were collected from respondents who are consumers of Emina cosmetics through questionnaires as the primary instrument, using both online and offline data collection techniques. Data analysis was performed using SPSS version 27, involving validity and reliability tests, classical assumption tests, and multiple regression analysis. The results indicate that electronic word of mouth, online reviews, and price sensitivity have a positive and significant partial influence on the purchase intention of Emina cosmetics. Simultaneously, these three variables also significantly influence purchase intention with a coefficient of determination (R^2) of 0.821, meaning that 82.1% of the variation in purchase intention can be explained by the three independent variables in the model. These findings are consistent with consumer behavior theory, communication theory, price sensitivity theory, and electronic word of mouth theory, which emphasize that consumer behavior is formed through communication processes, price perception, and digital information evaluation. Therefore, the results of this study are expected to provide practical contributions to cosmetic companies in developing more effective digital marketing strategies and strengthening consumer trust in the digital era.